Old tricks for new chips. (Economist, 2001)
After many years of looking for all sorts of ways to make their products run faster, chip designers are picking up on two technologies invented in the 1950s–60s. At the time, neither multi-threading nor asynchronous logic were competitive with conventional designs, but important uses have been found for both. Asynchronous logic is perfect for wireless devices and smartcards, while multi-threading can enhance the performance of database- and web-servers. Consequently, both of these technologies are destined for the marketplace.